2017
DOI: 10.1093/ejcts/ezx049
|View full text |Cite
|
Sign up to set email alerts
|

Association of circulating tumour cells with early relapse and 18F-fluorodeoxyglucose positron emission tomography uptake in resected non-small-cell lung cancers†

Abstract: Detection of CTCs 1 month after radical resection might be a useful marker to predict early recurrence in Stage I-III NSCLC. The SUVmax value of the primary tumour on preoperative PET scans was associated with the presence of CTC 1 month after the operation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 23 publications
2
12
0
Order By: Relevance
“…Hence, residual CTC after chemotherapy could be characterized in order to identify those morphological or genetic modification-inducing expression of genes and proteins conferring drug-resistance, such as the endothelial to mesenchymal transition observed in cancer stem cells [27,28]. In line with previous studies, we did not find a significant association between CTC and clinicopathological characteristics (e.g., age, gender, tobacco exposure, tumor size, and histologic subtype) in patients with advanced NSCLC [14,29,30]. Moreover, CTC count both at baseline and after 8 weeks, as well as their change during treatment, was not associated with tumor response according to morphologic criteria (RECIST 1.1), although a trend of significance with higher mean number of CTC for the PD group (p = 0.076) was evident.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…Hence, residual CTC after chemotherapy could be characterized in order to identify those morphological or genetic modification-inducing expression of genes and proteins conferring drug-resistance, such as the endothelial to mesenchymal transition observed in cancer stem cells [27,28]. In line with previous studies, we did not find a significant association between CTC and clinicopathological characteristics (e.g., age, gender, tobacco exposure, tumor size, and histologic subtype) in patients with advanced NSCLC [14,29,30]. Moreover, CTC count both at baseline and after 8 weeks, as well as their change during treatment, was not associated with tumor response according to morphologic criteria (RECIST 1.1), although a trend of significance with higher mean number of CTC for the PD group (p = 0.076) was evident.…”
Section: Discussionsupporting
confidence: 82%
“…Because our paper is the first in the era of checkpoint inhibitors investigating CTC and 18F-FDG PET parameters, comparison with other reports is not well applicable. Previously, some studies demonstrated a significant correlation between CTC and SUV value in patients with chemotherapy-naïve lung cancer [12][13][14]31]. On the contrary, Nygaard et al did not find any association between metabolic parameters and cell-free (cf) DNA, another tumor-derived biomarker [32].…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…The presence of CTCs2 was significantly correlated with preoperative tumour maximum standardised uptake value (SUV max ) on 18F-FDG PET/CT, pathological stage and surgical approach (thoracotomy or video-assisted thoracic surgery), and it was associated with recurrence-free survival (RFS) on multivariate analysis, independently of disease staging. CTCs2 were significantly correlated with a shorter RFS, and only SUV max was an independent predictor for the presence of CTCs2 [16].…”
mentioning
confidence: 88%
“…A single-centre prospective study in patients with untreated stage I-IIIA non-small cell lung cancer (NSCLC), who underwent radical resection, detected CTCs in 39.2% of patients before (CTCs1) and in 27.5% 1 month after the surgery (CTCs2) [16]. The presence of CTCs2 was significantly correlated with preoperative tumour maximum standardised uptake value (SUV max ) on 18F-FDG PET/CT, pathological stage and surgical approach (thoracotomy or video-assisted thoracic surgery), and it was associated with recurrence-free survival (RFS) on multivariate analysis, independently of disease staging.…”
mentioning
confidence: 99%